Information and communication communication technologies in the system of distance education - Hubarieva, Daria; Polisuchenko, Anna; Matviienko, Olena; Savenko, Oksana; Hrebnieva, Iryna; Zhalieiko, Daria (INT JOURNAL COMPUTER SCIENCE & NETWORK SECURITY-IJCSNS, 2021)
The purpose of this article is to consider the distance education system, its principles, features and means. One of its existing and promising tools is video conferencing. The article discusses the types of video conferencing, hardware and software, features and requirements for communication channels, types of information transmitted through these channels.
Keywords: Освіта дистанційна, освітня система, освітні програми дистанційні